2019
DOI: 10.1111/jam.14416
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiaeas a probiotic feed additive to non and pseudo‐ruminant feeding: a review

Abstract: The production of livestock and poultry faces major challenges to meet the global demand for meat and dairy products and eggs due to a steady increase in the world’s population and the ban of antibiotics in animal production. This ban has forced animal nutritionists to seek for natural alternatives to antibiotics. In this context, the yeast Saccharomyces cerevisiae has received considerable attention in the last decade. It has been reported that feed supplementation with live yeast cells improve feed efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 125 publications
(153 reference statements)
5
77
1
6
Order By: Relevance
“…As recently reviewed by Atanasov et al, several fungal polysaccharides, including yeast-derived β-glucans, are already being sold as commercial products due to their high bio-activity [ 18 ]. In the last few decades, a small number of studies investigated the effects of yeast-derived products on the intestinal health of pigs [ 19 ]. In a recent study that used an autolyzed dried yeast cell product, no effects were shown on caecal microbiota composition [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…As recently reviewed by Atanasov et al, several fungal polysaccharides, including yeast-derived β-glucans, are already being sold as commercial products due to their high bio-activity [ 18 ]. In the last few decades, a small number of studies investigated the effects of yeast-derived products on the intestinal health of pigs [ 19 ]. In a recent study that used an autolyzed dried yeast cell product, no effects were shown on caecal microbiota composition [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Saccharomyces cerevisiae (also known as 'baker's yeast') is considered as one of the most yeast species that are added to dietary formulations in poultry diets (Duarte et al, 2012). Saccharomyces cerevisiae contain substantial levels of digestible proteins, vitamins, magnesium, zinc and its wall have many characteristics such as polysaccharides α-D-mannan, chitin and β-D-glucan RESEARCH ARTICLE (Elghandour et al, 2019) which play an important role in microbial balance in intestine towards beneficial organisms. Furthermore, proliferation of tissues in intestine and lymphocytes with a rapid cell turnover depend mostly on dietary nucleotides where de novo synthesis of nucleotides cannot meet their demand (Alizadeh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The cell wall of S. cerevisiae has been shown to induce trophic effects on the intestinal mucosa of broilers, increase body weight gain, and improve feed efficiency ( Santin et al., 2001 ). Similarly, a recent review ( Elghandour et al., 2019 ) has discussed the application of live S. cerevisiae in poultry diets, whereby the organism improves feed efficiency and increases growth performance by causing competitive exclusion of pathogenic bacteria and stimulating the host immune system. In US patent 6,524,574, Spangler et al.…”
Section: Introductionmentioning
confidence: 99%